2.5D inversion of airborne EM data – a case study from new regional AEM data from the Mammoth Mines region, Queensland. Issue 1 (1st December 2019) - Walker, Greg; Paterson, Rod; Silic, Jovan; FitzGerald, Des
Summary: 2.5D (2D geology, 3D source) inversion of airborne electromagnetic (AEM) data has evolved into a routine and established practice on datasets from an array of applications. Large datasets may be inverted in days using conventional PC's, or cloud computing for faster results. The 2.5D inversions in this study were carried out using a highly modified adaptation of the ArjunAir program originally developed by the CSIRO and subsequently by AMIRA project P223F. The new program is called Moksha. Results are presented from a continental scale AEM regional mapping survey carried out by Geoscience Australia. 2.5D inversions performed in a study area in the Mammoth Mines mineral district of Queensland defined discrete conductivity anomalies on a line over the Mount Gordon Fault Zone, and imaged a series of steeply-dipping conductors on a nearby regional traverse. The study demonstrated the ability of 2.5D inversions to image steeply-dipping and folded geology, and present possible exploration targets, in a mineralised deformed terrane.